A preclinical pilot study on the effects of thermal ablation on lamb growth plates - Jäckle, Katharina; Lippross, Sebastian; Michel, Theresa Elisabeth; Kowallick, Johannes T.; Dullin, Christian; Lüders, Katja A.; Lorenz, Heiko M.; Tsaknakis, Konstantinos; Hell, Anna K. (Children, 2022)
(1) Background: Thermal ablation has been demonstrated to affect the bone growth of osteoid osteoma in adolescents. Growth modulation due to thermal heat in children is conceivable, but has not yet been established. We used lamb extremities as a preclinical model to examine the effect of thermal ablation on growth plates in order to evaluate its potential for axial or longitudinal growth modulation in pediatric patients. (2) Methods: Thermal ablation was performed by electrocautery on eight different growth plates of the legs and distal radii of a stillborn lamb. After treatment, target hits and the physical extent of the growth plate lesions were monitored using micro-computed tomography (micro-CT) and histology. (3) Results: Lesions and their physical extent could be quantified in 75% of the treated extremities. The histological analysis revealed that the disruption of tissue was confined to a small area and the applied heat did not cause the entire growth plate to be disrupted or obviously damaged. (4) Conclusions: Thermal ablation by electrocautery is minimally invasive and can be used for targeted disruption of small areas in growth plates in the animal model. The results suggest that thermal ablation can be developed into a suitable method to influence epiphyseal growth in children.